PENERAPAN MUHĀDATSAH AL-YAUMI DALAM PENINGKATAN KETERAMPILAN KALĀM PADA PONDOK PESANTREN DI SULAWESI SELATAN - Bahrun, Muhammad Farhan; Makmur, Reinizqy Mughniza; Azis, Abdul Jalil; Daroini, Slamet (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
The emergence of challenges in learning Arabic has driven academics to use complex and efficient methods that have a direct impact on their implementation. Therefore, one method that is considered capable of providing tangible results is "muhadatsah al-yaumi." In this paper, researchers will focus on how muhadatsah al-yaumi is implemented in practice, including textbooks, methods, techniques, and evaluations. The study aims to determine the percentage of user responses to the implementation of muhadatsah al-yaumi to enhance speaking skills. This research uses a mixed-methods approach with a qualitative approach to gather detailed data on the use of muhadatsah al-yaumi. Then, a quantitative approach is employed to measure the percentage of student responses to muhadtsah al-yaumi in improving speaking skills. The field research results show that the implementation of muhadatsah in Islamic boarding schools in South Sulawesi, specifically in two large boarding schools in two different districts (1) PPM Darul Falah Enrekang and (2) PPTQ As-Salam Sidrap, has yielded positive results, especially for users of muhadatsah al-yaumi, namely students from both boarding schools. This is supported by the satisfaction percentage of students regarding the muhadatsah program at PPM Darul Falah Enrekang and PPTQ As-Salam Sidrap, which shows that 8 out of 10 questionnaire variables indicate SATISFIED results, while the remaining 2 show NEUTRAL results. Therefore, it can be concluded that so far, the muhadatsah al-yaumi program has a positive and significant influence and is able to provide satisfaction to students by improving their speaking skills.